Increased Levels of CHI3L1 and HA Are Associated With Higher Occurrence of Liver Damage in Patients With Obstructive Sleep Apnea - Cai, Jingyao; Lyu, Xing; Huang, Peiying; Li, Shisheng; Chen, Ruohong; Chen, Zhiyang; Sun, Mei; Zeng, Ling; Wu, Fengxi; Hu, Min (Frontiers in Medicine, 2022)
Background Obstructive sleep apnea-hypopnea syndrome (OSA) may cause liver fibrosis, and liver fibrosis serum biomarkers plays an important role on the diagnosis of liver fibrosis. In addition, this study aimed to observe the changes of 4 serum markers and Chitinase 3-like protein 1 (CHII3L1) levels in OSA patients with different disease severity and explore their interactions. And then, we examined whether intermittent hypoxia (IH) exposure can activate hepatic stellate cell. Methods 74 OSA patients in Second Xiangya hospital from January 2021 to October 2021 was selected and categorized into mild, moderate, and severe groups according to AHI. In addition, 20 subjects were selected as the control group. Serum levels of liver fibrosis markers were determined by electrochemiluminescence immunoassay. Hepatic stellate cells were exposed to intermittent IH or normoxia (RA). Results were analyzed using the SPSS software. Results There was a significant increase in serum hyaluronic acid (HA), collagen type IV (CIV) and CHI3L1 levels in OSA patients compared with control group. Specifically, serum liver fibrosis markers HA, CIV and CHI3L1 levels were positively correlated with apnea-hypopnea index (AHI), but negatively correlated with the lowest saturation oxygen (LSaO2) respectively. The LX-2 cells (human hepatic stellate cell line) exposed to IH showed significant increases in fibrotic protein expression. Conclusion OSA might either directly or indirectly trigger or exacerbate liver fibrosis, possibly via IH-related pathways.